Pengaruh Pengembangan Sumber Daya Manusia Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Universitas Khairun - Fauzan Maulana Kodja; Abdullah W. Jabid; Marwan Man Soleman (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to examine the effect of human resource development (HR) and work discipline on employee performance. This type of research uses quantitative methods. The data collection technique in this research was carried out by distributing questionnaires to 77 civil servant respondents at the Rectorate of Khairun University, Ternate. The data analysis used in this study is Multiple Linear Analysis with the help of the SPSS 21 application. The results of data analysis in this study indicate that human resource development (HR) has a significant effect on employee performance and work discipline has a significant effect on employee performance.